2021
DOI: 10.15581/003.34.2.67-85
|View full text |Cite
|
Sign up to set email alerts
|

How the Internet has changed participation: Exploring distinctive preconditions of online activism

Abstract: The continuously growing number of people participating in Internet-based, online, political activism suggests that the latter has the potential to replace offline forms of unconventional political participation in the future. If that is the case, it is essential to understand the nature and objectives of such type of participation. This article addresses the question of distinctive preconditions of online activism. As a result of the mixed-effect logistic regression analysis of the European Social Survey data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 70 publications
0
9
0
Order By: Relevance
“…A first step in this strategic plan to expand the core business was the adaptation of the business towards digital distribution by relaunching Atresplayer Premium. Mediaset Spain also mentions the culmination of its transformation into an audiovisual company in 2020 (Mediaset, 2021a), presenting three axes: promoting profitability on the internet (Kopacheva, 2021) alongside the promotion of alliances in production and exploitation of audiovisual Alcolea-Díaz, G., Marín-Lladó, C. & Cervi, L. Expansion of the core business of traditional media companies in Spain through SVOD services content, all targeting diversification away from a dependence on advertising. The creation of the OTT services Mitele Plus and Mediterráneo Audiovisual can be framed within this strategic pillar, and it is within this context that the attempt to merge with its Italian parent company Mediaset can be justified.…”
Section: Discussionmentioning
confidence: 99%
“…A first step in this strategic plan to expand the core business was the adaptation of the business towards digital distribution by relaunching Atresplayer Premium. Mediaset Spain also mentions the culmination of its transformation into an audiovisual company in 2020 (Mediaset, 2021a), presenting three axes: promoting profitability on the internet (Kopacheva, 2021) alongside the promotion of alliances in production and exploitation of audiovisual Alcolea-Díaz, G., Marín-Lladó, C. & Cervi, L. Expansion of the core business of traditional media companies in Spain through SVOD services content, all targeting diversification away from a dependence on advertising. The creation of the OTT services Mitele Plus and Mediterráneo Audiovisual can be framed within this strategic pillar, and it is within this context that the attempt to merge with its Italian parent company Mediaset can be justified.…”
Section: Discussionmentioning
confidence: 99%
“…Dozens of empirical studies (see Section 2 for examples) on explanatory factors of civic engagement have been conducted since the publication of "Voice and 1 Although, alternative arguments have also been raised. For example, it has been suggested that high levels of participation lead to a fragmentation of the political process, which makes it harder to reach a consensus and implement policies (Lijphart, 1977).…”
Section: Theoretical Traditions Of Political-participation Researchmentioning
confidence: 99%
“…The Civic Voluntarism Model (CVM) (Verba et al, 1995) as described by Verba et al is not a comprehensive model of political participation. Instead, it is a model of factors that enhance (rather than explain) participation 1 . The original version of CVM (summarised by the diagram in Figure 2.1) includes three groups of factors that enhance political participation.…”
Section: Cvm As Described In "Voice and Equality"mentioning
confidence: 99%
See 2 more Smart Citations